Ikenberry, Ed., American Foreign Policy - Theoretical Essays - Redinger, Matthew (Teaching History: A Journal of Methods, 2011)
In American Foreign Policy: Theoretical Essays, G. John Ikenberry, the Albert G. Milbank Professor of Politics and International Affairs at Princeton University, presents readers with a comprehensive overview of the most critical topics in United States foreign relations. Ikenberry brings his significant scholarly experience to bear in the editing of a volume of essays written by acknowledged experts in the field of U. S. foreign policy on topics as varied as U.S. foreign policy itself.